Broker-supported and constraint-based infrastructure for collaborative systems - Zhang, Peinan (ProQuest Dissertations & Theses, 1996)
A collaborative system is much more complicated than a single user system due to a variety of collaboration capability, distribution features and interaction requirements. It is desirable for such a system to allow extensible sharing regardless of location and heterogeneity. Concurrent interactions with shared objects require facilities to provide real-time collaboration awareness and maintain system consistency. This thesis is a step towards developing generic models and enabling infrastructure to provide this support so as to ease the construction of collaborative systems. In this dissertation, we propose: (1) a hierarchical session model to provide a flexible sharing capability so that collaborations become extensible and integrable, (2) a distribution model to enable communication among heterogeneous collaboration participants or application clients/servers, and (3) an object-based constraint management model which supports constraint relationships among object methods as well as object data fields; it integrates constraint solving methods with concurrency control, so that the constraint relationships can be maintained even in a heterogeneous environment and under concurrent interactions. Based on these models, we have designed a broker-supported and constraint-based enabling infrastructure which includes the necessary facilities for collaboration control, distribution control, and interaction control in collaborative systems. We have further implemented our design in the Shastra distributed and collaborative environment. Applications developed in Shastra demonstrate how the models and the infrastructure facilitate the construction of collaborative systems.